Avaliação da gestão da coleta seletiva e da organização dos catadores de materiais recicláveis no município de Martinópolis - São Paulo, Brasil: indicadores e índices de sustentabilidade - Cristofoli, Giovanna Rocha [UNESP]; Santos, Leandro Lopes dos [UNESP] (Universidade Estadual Paulista (Unesp), 2022)
Currently, solid waste plays a prominent category in debates on issues related to the environment, mainly because its generation is linked to almost all human activities and its effective and/or potential risk against public health and degradation of environmental quality. In this sense, one of the several ways to treat these solid wastes, especially those classified as Urban Solid Waste - USW, is by means of recycling, which, together with the selective collection, presents a gain factor in the quality and quantity of the raw material available. With this, the objective of the present study is to evaluate the situation linked to the selective collection and organization of collectors of recyclable materials in the municipality of Martinópolis - São Paulo, Brazil, considering the indicators and indices of sustainability proposed by Besen et al. (2017). Thus, to obtain the data, we relied on the use of forms and interviews that occurred through videoconferencing due to the pandemic caused by the SARS-CoV-2 virus, with the support of representatives of the Secretariat of Environment of the aforementioned municipality, as well as the Cooperative of Work of the Collectors of Recyclable Materials of Martinópolis - COOPERMART. In this context, it was found that both the index of sustainability of selective collection and the index of organization of the collectors present, respectively, the value of 0.54 and 0.74. Both values present the classification type "Favorable", indicating that the municipal management and the organization of the collectors are investing in sustainability. However, when analyzing the indicators of both segments of the research individually and disregarding the general calculation of the indexes, it was found that the predominant classification in the evaluation of selective collection is of the type "Unfavorable" with 43.75% and "Very Unfavorable" with 25%, while in the organization of the collectors of recyclable materials we have that 42.86% of the indicators obtained classification of the type "Unfavorable". Given this, and based on the respective indicators and their classifications matrices were developed that denote a set of propositions that aim to improve and develop an appropriate management of selective collection and organization of the collectors of recyclable materials of the city of Martinópolis - SP, Brazil aiming at sustainability.

Atualmente, os resíduos sólidos desempenham uma categoria de destaque nos debates de assuntos vinculados ao meio ambiente, principalmente pelo fato de sua geração estar atrelada com quase todas atividades humanas e por seu efetivo e/ou potencial risco contra à saúde pública e de degradação da qualidade ambiental. Neste sentido, uma das diversas formas de tratamento desses resíduos sólidos, em destaque para aqueles classificados como Resíduos Sólidos Urbanos – RSU, é por intermédio da reciclagem, que atrelada à coleta do tipo seletiva apresenta um fator de ganho na qualidade e na quantidade da matéria-prima disponível. Com isso, o objetivo do presente estudo consiste em avaliar a conjuntura vinculada à coleta seletiva e de organização dos catadores de materiais recicláveis do município de Martinópolis – São Paulo, Brasil, considerando os indicadores e índices de sustentabilidade propostos por Besen et al. (2017). Assim, para obtenção dos dados, contou-se com a utilização de formulários e de entrevistas que ocorreram por intermédio de videoconferências em decorrência da pandemia ocasionada pelo vírus SARS-CoV-2, contando com o apoio de representantes da Secretaria do Meio Ambiente do supracitado município, bem como da Cooperativa de Trabalho dos Catadores de Materiais Recicláveis de Martinópolis – COOPERMART. Neste contexto, averiguou-se que tanto o índice de sustentabilidade da coleta seletiva quanto o índice de organização dos catadores apresentam, respectivamente, o valor de 0,54 e 0,74. Ambos os valores apresentam a classificação do tipo "Favorável", indicando que a gestão do município e a organização dos catadores estão investindo em sustentabilidade. Contudo, ao analisar os indicadores, de ambos segmentos da pesquisa individualmente e desconsiderando o cálculo geral dos índices, verificou-se que a classificação predominante na avaliação da coleta seletiva é do tipo “Desfavorável” com 43,75% e “Muito Desfavorável” com 25%, enquanto que na organização dos catadores de materiais recicláveis têm-se que 42,86% dos indicadores obtiveram classificação do tipo “Desfavorável”. Diante disso, e com base nos respectivos indicadores e suas classificações elaborou-se matrizes que denotam um conjunto de proposituras que visam aperfeiçoar e desenvolver uma adequada gestão da coleta seletiva e de organização dos catadores de materiais recicláveis do município de Martinópolis – SP, Brasil visando à sustentabilidade.
Evaluation of the management of selective collection and the organization of collectors of recyclable materials in the municipality of Martinópolis - São Paulo, Brazil: sustainability indicators and indexes
Evaluación de la gestión de la recogida selectiva y de la organización de los recolectores de materiales reciclables en el municipio de Martinópolis - São Paulo, Brasil: indicadores e índices de sostenibilidad
Keywords: Sustainability indicators and indexes; Selective collection management; Organization of recyclable materials collectors; Indicadores e índices de sustentabilidade; Gestão de coleta seletiva; Organização dos catadores de materiais recicláveis; Engenharia ambiental; Meio ambiente; Resíduos sólidos; Cooperativas; Sustentabilidade